A covering property with respect to generalized preopen sets - Ajoy Mukharjee (Boletim da Sociedade Paranaense de Matemática, 2019)
In this paper, we introduce and study the notion of $μ$-precompact spaces on the observation that each $μ$-preopen set of a generalized topological space is contained in a $μ$-open set. The $μ$-precompactness is weaker than $μ$-compactness but stronger than weakly $μ$-compactness of generalized topological spaces.